A sodium manganate positive electrode material with S / N dual doping at the interface and its preparation method and application

By introducing S and N elements into the sodium manganate positive electrode material to form an interface S/N double-doped structure, the problem of insufficient material conductivity and structural stability is solved, and the electrochemical performance and cyclic stability of the material are significantly improved.

CN115548280BActive Publication Date: 2025-04-22CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211021703.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-24
Publication Date
2025-04-22
Estimated Expiration
2042-08-24

AI Technical Summary

Technical Problem

The sodium manganate positive electrode material has low conductivity and poor structural stability in the electrochemical process, resulting in low reversibility of the material.

Method used

By introducing non-metallic elements S and N of the same clan, a sodium manganate positive electrode material with an interface S/N doped interface is formed to improve the conductivity and structural stability of the material. The specific method includes oxidative sintering of the sodium-containing compound and the manganese salt, followed by secondary sintering under an atmosphere of hydrogen sulfide and ammonia, to achieve bi-element doping of S and N.

Benefits of technology

It improves the electrochemical activity and conductivity of the material, improves the structural stability and corrosion resistance of the material, and significantly improves the circulation stability and battery performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115548280B_ABST
    Figure CN115548280B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion battery materials and discloses an interface S / N dual-doped sodium manganate positive electrode material, whose molecular formula is Na z Mn(O 2‑x‑y S x N y ), wherein 0.005≤x≤0.02, 0.005≤y≤0.02, 0.5≤z≤1. By doping S and N simultaneously in the sodium manganate material, the co-doping of the interface of the two anions greatly improves the conductivity of the material itself, and improves the structural stability and corrosion resistance of the surface of the material. Also disclosed is its preparation method and application. The method adopts a vapor phase sintering method to directly form an S / N co-doped interface layer on the surface of the sodium manganate, which can effectively improve the conductivity of the material. The interface S / N dual-doped sodium manganate material prepared by the present invention has a consistent particle size and a uniform distribution of elements in the interface layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion battery manufacturing, and specifically relates to an interface S / N dual-doped sodium manganate positive electrode material and a preparation method and application thereof. Background Art

[0002] As a "post-lithium-ion battery", sodium-ion batteries have similar working principles and battery devices to lithium-ion batteries. Metallic sodium has abundant mineral resources on the surface, which will greatly reduce the cost of batteries. Therefore, sodium-ion batteries were once considered to be the most ideal choice for secondary batteries. With more and more research on sodium-ion batteries, people have found that there are still many problems in its practical application. Taking the commonly used sodium manganate as an example, there are mainly the following problems. For example, due to the large ionic radius of sodium ions, the stability of battery materials during the electrochemical cycle is poor, resulting in low reversibility of the material. Furthermore, the poor conductivity of the electrode limits the diffusion of ions and electrons. Therefore, exploring the synthesis of materials with higher conductivity and structural stability will effectively improve the structure and performance of the material itself.

[0003] Currently mature sodium manganate materials have the advantages of low cost and high stability. However, their poor conductivity still makes them face many challenges in practical applications. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology, solve the problems of low conductivity and poor structural stability of sodium manganate positive electrode materials in the electrochemical process, improve the conductivity and cycle stability of the material, and provide an interface S / N dual-doped sodium manganate positive electrode material and its preparation method and application.

[0005] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0006] An interface S / N dual-doped sodium manganate positive electrode material, the molecular formula of which is Na z Mn(O 2-x-y S x N y ), where 0.005≤x≤0.02, 0.005≤y≤0.02, 0.5≤z≤1.

[0007] Preferably, the size of the sodium manganate material is as follows: length 1-3 μm, width 0.5-1.5 μm, thickness 0.2-0.5 μm. The morphology of the sodium manganate material before and after doping is polygonal micron flakes.

[0008] Based on a general inventive concept, the present invention also provides a method for preparing an interfacial S / N dual-doped sodium manganate positive electrode material, comprising the following steps:

[0009] (1) subjecting the sodium-containing compound and the manganese salt to an oxidative sintering treatment to obtain a sodium manganate positive electrode material;

[0010] (2) The sodium manganate positive electrode material is placed in an atmosphere containing hydrogen sulfide and ammonia for secondary sintering to obtain the interface S / N dual-doped sodium manganate positive electrode material.

[0011] In the above preparation method, preferably, in step (1), the sodium-containing compound is a sodium salt or sodium oxide, and the sodium salt is one or more of sodium acetate, sodium oxalate, sodium nitrate, and sodium carbonate; and the manganese salt is one or more of manganese acetate, manganese oxalate, manganese nitrate, and manganese carbonate.

[0012] Preferably, in step (1), the molar ratio of the manganese salt to the manganese and sodium elements of the sodium-containing compound is 1:(1.03-1.05).

[0013] Preferably, in step (1), the atmosphere of the oxidative sintering treatment is oxygen or air atmosphere.

[0014] Preferably, in step (1), the heating rate of the oxidation sintering treatment is 2-5°C / min, and the sintering process includes low-temperature pre-sintering and high-temperature sintering; the temperature of the low-temperature pre-sintering is 300-500°C, and the time is 2-8h; the temperature of the high-temperature sintering is 800-1000°C, and the time is 6-24h.

[0015] Preferably, in step (2), the atmosphere composition in the secondary sintering is mainly hydrogen sulfide and ammonia; the gas flow rates of the hydrogen sulfide and ammonia are 100-200 mL / min, respectively.

[0016] More preferably, in step (2), the gas flow rate of hydrogen sulfide is 200 mL / min, and the gas flow rate of ammonia is 100 mL / min.

[0017] Different gas flow rates will cause different amounts of element doping, and different doping ratios will directly affect the overall performance of the material. Since S has a higher electronegativity than N and is in the same family as oxygen, the corresponding structural characteristics are also very consistent, but also different. The larger ion radius of S will cause more defects in the structure, a larger interlayer spacing, and better for the transmission of sodium ions.

[0018] Preferably, in step (2), the heating rate of the secondary sintering is 2-5°C / min, the temperature of the secondary sintering is 500-800°C, and the time is 2-10h.

[0019] Based on a general inventive concept, the present invention also provides an application of an interfacial S / N dual-doped sodium manganate positive electrode material in the preparation of a sodium ion battery.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention can effectively improve the electrochemical activity of the material by introducing the non-metallic element S of the same family; by introducing the element N, short-range defects can be created, void charge carriers can be introduced, and the conductivity of the material can be improved; by simultaneously doping S and N in the sodium manganate material, the doping of these two anions can improve the conductivity of the material itself, and improve the structural stability and corrosion resistance of the material surface.

[0022] (2) The present invention performs doping by direct sintering in an atmosphere of hydrogen sulfide and ammonia. The doping method is simple and easy to implement, thereby achieving simultaneous doping of two elements and effectively ensuring the uniformity of doping. The prior art adopts the step-by-step doping of N and S elements, which is likely to cause an uneven distribution phenomenon with more N doping inside and more S doping outside. However, the direct sintering doping method of the present invention allows the two doping elements to be more uniformly doped step by step, the internal and external structural consistency is stronger, and the electrochemical performance stability will also be more superior.

[0023] (3) The preparation of the present invention is to synthesize the interfacial S / N co-doped sodium manganate material by a one-step gas phase sintering method. The prepared material has uniform particles and uniform element distribution, which improves the structural stability and corrosion resistance of the material surface. In addition, the process is simple, the flow is short, the raw materials are easily available, no toxic or harmful substances are generated during the preparation process, and large-scale production is easy to achieve. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 This is the SEM of the positive electrode material product in Example 3 of the present invention. DETAILED DESCRIPTION

[0026] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0027] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0029] Embodiment 1:

[0030] A method for preparing an interface S / N dual-doped sodium manganate positive electrode material of the present invention comprises the following steps:

[0031] (1) 0.05 mol MnCO3 and 0.026 mol Na2CO3 powders were mixed uniformly by ball milling, and then pre-calcined at 300°C for 2 h in a muffle furnace, and then further sintered at 900°C for 10 h to obtain a sodium manganate positive electrode material (powder);

[0032] (2) The obtained sodium manganate positive electrode material was transferred into a tubular furnace, and a secondary sintering was performed in an atmosphere containing hydrogen sulfide and ammonia at a flow rate of 100 mL / min. The sintering temperature was 600° C. and the sintering was performed for 4 h to obtain the interface S / N dual-doped Na 0.67 MnO 1.99 S 0.005 N 0.005 Positive electrode material. The dimensions of the positive electrode material are as follows: 1-3 μm in length, 0.5-1.5 μm in width, and 0.2-0.5 μm in thickness.

[0033] Na with interface S / N dual doping 0.67 MnO 1.99 S 0.005 N 0.005 It is the active material of the positive electrode material, and is mixed with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) is used as the solvent, and the mixture is placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a slurry. The slurry is coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for 4h, punched into a pole piece with a diameter of 12mm, and then dried at 105°C in a vacuum drying oven for 4h, placed in a glove box filled with argon atmosphere with a water content and oxygen content of less than 0.1ppm for 4h to reduce the moisture adsorbed by the pole piece during the transfer process, and then assembled into a CR2032 button battery in the glove box. The metallic sodium is rolled into thin sheets and punched into 14mm round sodium sheets to serve as the negative electrode. A 1mol / L NaClO4 solution is used as the electrolyte, and a glass fiber membrane with a diameter of 16mm is used as the diaphragm.

[0034] After the battery was assembled and aged for 12 hours, the charge and discharge tests were carried out at different potentials. The discharge capacity of the calcined sample after 100 cycles at a voltage of 2-4V and a current density of 1C was 121.2mA hg -1 , the capacity retention rate is 89.6%.

[0035] Embodiment 2:

[0036] A method for preparing an interface S / N dual-doped sodium manganate positive electrode material of the present invention comprises the following steps:

[0037] (1) 0.05 mol MnCO3 and 0.026 mol Na2CO3 powders were mixed uniformly by ball milling, and then pre-calcined at 300°C for 2 h in a muffle furnace, and then further sintered at 900°C for 10 h to obtain a sodium manganate positive electrode material (powder);

[0038] (2) The obtained sodium manganate positive electrode material was transferred into a tubular furnace, and hydrogen sulfide with a flow rate of 100 mL / min and ammonia with a flow rate of 200 mL / min were simultaneously introduced into the furnace for secondary sintering. The sintering temperature was 600 ° C and the sintering was performed for 4 h to obtain the interface S / N dual-doped Na 0.67 MnO 1.991 S 0.003 N 0.006 Positive electrode material. The dimensions of the positive electrode material are as follows: 1-3 μm in length, 0.5-1.5 μm in width, and 0.2-0.5 μm in thickness.

[0039] Na with interface S / N dual doping 0.67 MnO 1.991 S 0.003 N 0.006 It is the active material of the positive electrode material, and is mixed with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) is used as the solvent, and the mixture is placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a slurry. The slurry is coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for 4h, punched into a pole piece with a diameter of 12mm, and then dried at 105°C in a vacuum drying oven for 4h, placed in a glove box filled with argon atmosphere with a water content and oxygen content of less than 0.1ppm for 4h to reduce the moisture adsorbed by the pole piece during the transfer process, and then assembled into a CR2032 button battery in the glove box. The metallic sodium is rolled into thin sheets and punched into 14mm round sodium sheets to serve as the negative electrode. A 1mol / L NaClO4 solution is used as the electrolyte, and a glass fiber membrane with a diameter of 16mm is used as the diaphragm.

[0040] After the battery was assembled and aged for 12 hours, the charge and discharge tests were carried out at different potentials. The discharge capacity of the calcined sample after 100 cycles at a voltage of 2-4V and a current density of 1C was 110.3mA hg -1 , the capacity retention rate is 81.5%.

[0041] Embodiment 3:

[0042] A method for preparing an interface S / N dual-doped sodium manganate positive electrode material of the present invention comprises the following steps:

[0043] (1) 0.05 mol MnCO3 and 0.026 mol Na2CO3 powders were mixed uniformly by ball milling, and then pre-calcined at 300°C for 2 h in a muffle furnace, and then further sintered at 900°C for 10 h to obtain a sodium manganate positive electrode material (powder);

[0044] (2) The obtained sodium manganate positive electrode material was transferred into a tubular furnace, and hydrogen sulfide with a flow rate of 200 mL / min and ammonia with a flow rate of 100 mL / min were simultaneously introduced into the furnace for secondary sintering. The sintering temperature was 600 ° C and the sintering was performed for 4 h to obtain the interface S / N dual-doped Na 0.67 MnO 1.991 S 0.006 N 0.003 Cathode materials such as Figure 1 shown.

[0045] Depend on Figure 1 It can be seen that the present invention forms a S / N co-doped interface layer on the surface of sodium manganate, and the particle size is consistent, and the elements of the interface layer are evenly distributed. The dimensions of the positive electrode material are as follows: length is 1-3 μm, width is 0.5-1.5 μm, and thickness is 0.2-0.5 μm.

[0046] Na with interface S / N dual doping 0.67 MnO 1.991 S 0.006 N 0.003It is the active material of the positive electrode material, and is mixed with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) is used as the solvent, and the mixture is placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a slurry. The slurry is coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for 4h, punched into a pole piece with a diameter of 12mm, and then dried at 105°C in a vacuum drying oven for 4h, placed in a glove box filled with argon atmosphere with a water content and oxygen content of less than 0.1ppm for 4h to reduce the moisture adsorbed by the pole piece during the transfer process, and then assembled into a CR2032 button battery in the glove box. The metallic sodium is rolled into thin sheets and punched into 14mm round sodium sheets to serve as the negative electrode. A 1mol / L NaClO4 solution is used as the electrolyte, and a glass fiber membrane with a diameter of 16mm is used as the diaphragm.

[0047] After the battery was assembled and aged for 12 hours, the charge and discharge tests were carried out at different potentials. The discharge capacity of the calcined sample after 100 cycles at a voltage of 2-4V and a current density of 1C was 125.2mA hg -1 , the capacity retention rate is 90.8%.

[0048] Embodiment 4:

[0049] A method for preparing an interface S / N dual-doped sodium manganate positive electrode material of the present invention comprises the following steps:

[0050] (1) 0.05 mol MnCO3 and 0.026 mol Na2CO3 powders were mixed uniformly by ball milling, and then pre-calcined at 300°C for 2 h in a muffle furnace, and then further sintered at 900°C for 10 h to obtain a sodium manganate positive electrode material (powder);

[0051] (2) The obtained sodium manganate positive electrode material was transferred into a tubular furnace, and hydrogen sulfide with a flow rate of 100 mL / min and ammonia with a flow rate of 100 mL / min were simultaneously introduced into the furnace for secondary sintering. The sintering temperature was 600°C and the sintering time was 8 h to obtain the interface S / N dual-doped Na 0.67 MnO 1.984 S 0.008 N 0.008 Positive electrode material. The dimensions of the positive electrode material are as follows: 1-3 μm in length, 0.5-1.5 μm in width, and 0.2-0.5 μm in thickness.

[0052] Na with interface S / N dual doping 0.67 MnO 1.984 S 0.008 N 0.008It is the active material of the positive electrode material, and is mixed with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) is used as the solvent, and the mixture is placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a slurry. The slurry is coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for 4h, punched into a pole piece with a diameter of 12mm, and then dried at 105°C in a vacuum drying oven for 4h, placed in a glove box filled with argon atmosphere with a water content and oxygen content of less than 0.1ppm for 4h to reduce the moisture adsorbed by the pole piece during the transfer process, and then assembled into a CR2032 button battery in the glove box. The metallic sodium is rolled into thin sheets and punched into 14mm round sodium sheets to serve as the negative electrode. A 1mol / L NaClO4 solution is used as the electrolyte, and a glass fiber membrane with a diameter of 16mm is used as the diaphragm.

[0053] After the battery was assembled and aged for 12 hours, the charge and discharge tests were carried out at different potentials. The discharge capacity of the calcined sample after 100 cycles at a voltage of 2-4V and a current density of 1C was 117.3mA hg -1 , the capacity retention rate is 82.1%.

[0054] Embodiment 5:

[0055] A method for preparing an interface S / N dual-doped sodium manganate positive electrode material of the present invention comprises the following steps:

[0056] (1) 0.05 mol MnCO3 and 0.026 mol Na2CO3 powders were mixed uniformly by ball milling, and then pre-calcined at 300°C for 2 h in a muffle furnace, and then further sintered at 900°C for 10 h to obtain a sodium manganate positive electrode material (powder);

[0057] (2) The obtained sodium manganate positive electrode material was transferred into a tubular furnace, and hydrogen sulfide with a flow rate of 100 mL / min and ammonia with a flow rate of 100 mL / min were simultaneously introduced into the furnace for secondary sintering. The sintering temperature was 600 ° C for 2 h to obtain the interface S / N dual-doped Na 0.67 MnO 1.994 S 0.003 N 0.003 Positive electrode material. The dimensions of the positive electrode material are as follows: 1-3 μm in length, 0.5-1.5 μm in width, and 0.2-0.5 μm in thickness.

[0058] Na with interface S / N dual doping 0.67 MnO 1.994 S 0.003 N 0.003It is the active material of the positive electrode material, and is mixed with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) is used as the solvent, and the mixture is placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a slurry. The slurry is coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for 4h, punched into a pole piece with a diameter of 12mm, and then dried at 105°C in a vacuum drying oven for 4h, placed in a glove box filled with argon atmosphere with a water content and oxygen content of less than 0.1ppm for 4h to reduce the moisture adsorbed by the pole piece during the transfer process, and then assembled into a CR2032 button battery in the glove box. The metallic sodium is rolled into thin sheets and punched into 14mm round sodium sheets to serve as the negative electrode. A 1mol / L NaClO4 solution is used as the electrolyte, and a glass fiber membrane with a diameter of 16mm is used as the diaphragm.

[0059] After the battery was assembled and aged for 12 hours, the charge and discharge tests were carried out at different potentials. The discharge capacity of the calcined sample after 100 cycles at a voltage of 2-4V and a current density of 1C was 105.5mA hg -1 , the capacity retention rate is 77.8%.

[0060] Comparative Example 1:

[0061] A method for preparing a sodium manganate positive electrode material comprises the following steps:

[0062] 0.05 mol MnCO3 and 0.026 mol Na2CO3 were powdered and mixed evenly by ball milling, and then placed in a muffle furnace for pre-calcination at 300°C for 2 hours, and then further sintered at 900°C for 10 hours to obtain a sodium manganate positive electrode material.

[0063] Take Na 0.67MnO2 is the active material of the positive electrode material, and is mixed with the conductive agent acetylene black (AB) and the binder polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) is used as the solvent, and the mixture is placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a slurry. The slurry is coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for 4h, punched into a pole piece with a diameter of 12mm, and then dried at 105°C in a vacuum drying oven for 4h. It is placed in a glove box filled with argon atmosphere with a water content and oxygen content of less than 0.1ppm for 4h to reduce the moisture adsorbed by the pole piece during the transfer process, and then assembled into a CR2032 button battery in the glove box. The metallic sodium is rolled into thin sheets and punched into 14mm round sodium sheets to serve as the negative electrode. A 1mol / L NaClO4 solution is used as the electrolyte, and a glass fiber membrane with a diameter of 16mm is used as the diaphragm.

[0064] After the battery was assembled and aged for 12 hours, the charge and discharge tests were carried out at different potentials. The discharge capacity of the calcined sample after 100 cycles at a voltage of 2-4V and a current density of 1C was 63.7mA hg -1 , the capacity retention rate is 48.5%.

[0065] The above contents are only basic descriptions of the concept of the present invention, and any equivalent changes made according to the technical solution of the present invention shall fall within the protection scope of the present invention.

Claims

1. An interface S / N dual-doped sodium manganate positive electrode material, characterized in that: Its molecular formula is Na z Mn(O 2-x-y S x N y ), where 0.005≤x≤0.02, 0.005≤y≤0.02, 0.5≤z≤1.

2. The interfacial S / N dual-doped sodium manganate positive electrode material according to claim 1, characterized in that: The dimensions of the sodium manganate material are as follows: 1-3 μm in length, 0.5-1.5 μm in width, and 0.2-0.5 μm in thickness.

3. A method for preparing an interface S / N dual-doped sodium manganate positive electrode material, characterized in that: The following steps are involved: (1) subjecting the sodium-containing compound and the manganese salt to an oxidative sintering treatment to obtain a sodium manganate positive electrode material; (2) The sodium manganate positive electrode material is placed in an atmosphere containing hydrogen sulfide and ammonia for secondary sintering to obtain the interface S / N dual-doped sodium manganate positive electrode material.

4. The method for preparing the interfacial S / N dual-doped sodium manganate positive electrode material according to claim 3, characterized in that: In step (1), the sodium-containing compound is a sodium salt or sodium oxide, the sodium salt is one or more of sodium acetate, sodium oxalate, sodium nitrate, and sodium carbonate; the manganese salt is one or more of manganese acetate, manganese oxalate, manganese nitrate, and manganese carbonate.

5. The method for preparing the interfacial S / N dual-doped sodium manganate positive electrode material according to claim 3, characterized in that: In step (1), the molar ratio of the manganese salt to the manganese sodium element of the sodium-containing compound is 1:(1.03-1.05), and the atmosphere of the oxidative sintering treatment is oxygen or air atmosphere.

6. The method for preparing the interfacial S / N dual-doped sodium manganate positive electrode material according to claim 3, characterized in that: In step (1), the heating rate of the oxidation sintering treatment is 2-5°C / min, and the sintering process includes low-temperature pre-sintering and high-temperature sintering; the temperature of the low-temperature pre-sintering is 300-500°C, and the time is 2-8h; the temperature of the high-temperature sintering is 800-1000°C, and the time is 6-24h.

7. The method for preparing the interfacial S / N dual-doped sodium manganate positive electrode material according to claim 3, characterized in that: In step (2), the atmosphere composition in the secondary sintering is mainly hydrogen sulfide and ammonia; the gas flow rates of the hydrogen sulfide and ammonia are 100-200 mL / min respectively.

8. The method for preparing the interfacial S / N dual-doped sodium manganate positive electrode material according to claim 7, characterized in that: In step (2), the gas flow rate of hydrogen sulfide is 200 mL / min, and the gas flow rate of ammonia is 100 mL / min.

9. The method for preparing the interfacial S / N dual-doped sodium manganate positive electrode material according to any one of claims 3 to 8, characterized in that: In step (2), the heating rate of the secondary sintering is 2-5°C / min, the temperature of the secondary sintering is 500-800°C, and the time is 2-10h.

10. Use of the sodium manganate positive electrode material according to claim 1 or 2 or the sodium manganate positive electrode material prepared by the preparation method according to any one of claims 3 to 9 in the preparation of a sodium ion battery.

Citation Information

Patent Citations

  • Improvements in or relating to electrochemical cells

    AU2008203082A1

  • A water solution Na ion chargeable battery

    CN101087018A